CONTROL OF MASTITIS IN LACTATING COWS USING Staphylococcus aureus BACTERIN APPLIED REPEATEDLY DURING LACTATION - ALBERTON, Luiz Rômulo (Scientia Agraria, 2000)
The efficiency of Staphylococcus aureus bacterin in the control of mastitis in cows was evaluated in forty-five lactating Jersey cows which received the vaccine repeatedly for sixteen weeks. The vaccine was made from strains S.aureus coagulase-positive isolated from the same herd tested. The bacteria were inactivated with formalin and 2,5% aluminum hydroxide was added as adjuvant. The animals were divided in three groups of fifteen animals as follows: control, without any treatment; weekly group, where the animals received weekly injections of 3,0 ml of the vaccine, subcutaneously in the region of the mammary lymph-node; and the biweekly group, which received the same treatment as the previous one in two-week intervals. Milk production was evaluated daily. Samples of milk were collected weekly and submitted to the following tests: California Mastitis Test (CMT); Somatic CeIls Count (SCC) and mensuration of total solids, lactose, fat and protein contents. Samples positive for mastitis in CMT were submitted to bacteriological exams for identification of the bacteria involved. FinaIly, an evaluation was made of the economic impact the vaccination might have comparing the control and weekly groups. The data attained were extrapolated for one year. Results demonstrated that the percentage of milk samples with CCS inferior to 3 x 105 cells/ml and 5 x 105 cells/ml was larger in the weekly group (p≤0.05) than in other groups. The percentage of positive samples to CMT was 60.00% smaller (p≤0.05) in the weekly group than in control (9.16% and 22.70%, respectively). The percentages of moderate to severe infections accordingly to CMT were smaller (p≤0.05) in the weekly group (35.98%) than control (63.33%) and biweekly groups (57.43%) Comparing to the control group, milk production was 7.10% larger in the weekly group and the total solids contents was larger in the weekly and biweekly groups. However, lactose content was larger in the biweekly group than in the weekly group. Fat and protein contents did not vary significantly among the groups. During the experiment, in all the groups, cases of subclinical mastitis were more frequent than other forms of the disease, reaching 81.46% of the total of cases, and Staphylococcus aureus was the most frequent bacteria isolated. The percentage of S. aureus subclinical mastitis cases was smaller in the weekly group (25.00%) than in control group (32.25%) and in the biweekly group (43.75%). The economic analysis demonstrated that, in control group, the costs represented by milk discarding and treatment of mastitis cases would reach US$ 2,636.28 annually. On the other hand, in the group vaccinated weekly, could have a profit of US$ 841.59 if the expenses with vaccine and the increase in milk production are considered. It was concluded that bacterin made from S. aureus isolated from the same herd and containing aluminum hydroxide as adjuvant. when injected SQ repeatedly at one-.week intervals in the mammary lymph-node region during the course of lactation, is capable to decrease both the prevalence and the severity of mastitis in Iactating cows, and can improve the quality of milk and to reduced financial losses caused by the disease.